Management of Infections in Palliative Care Patients at the End-of-Life and Active Process of Death: A Brazilian Retrospective Study - Isabela Fernandes de Aguiar Tonetto; Angelita Maria Stabile; Dieyeni Yuki Kobayasi; Rita de Cássia Quaglio; Ana Carolina de Souza; Fabiana Bolela (Palliative Medicine Reports)
Background: There is a lack of specific studies on the management of infections in patients receiving palliative care (PC) in the final stages of life and during the active process of death, related to specific nursing care. There is clinical and social importance as patients in PC represent a vulnerable population, and adequate management of infections is crucial to improve quality of life and the experience of comfort. Objective: This study analyzed how infections are managed in patients undergoing PC at the end-of-life and in the active process of death in two hospital health services. Design: This is an observational, analytical, and retrospective study. Settings: Data collection took place in two hospitals that assist individuals who are hospitalized under PC, located in Brazil, in a city in the interior of the state of São Paulo. Measurements and Results: The sample consisted of 113 medical records, in which the oncological diagnosis was the most prevalent. There was a predominance of infection diagnoses based on the patient’s clinical symptoms, the main focus being the pulmonary, in individuals at the end-of-life. The management of infection in the study sample occurred through care and procedures that generate physical discomfort, however aiming at relieving symptoms. Such findings must be documented, as they invite us to reflect on our practical attitudes and what it means to be comfortable for these people, making it possible to incorporate this information into the design of interventions focused on enhancing the experience of comfort.